2022
DOI: 10.4103/jllr.jllr_20_22
|View full text |Cite
|
Sign up to set email alerts
|

Motorized Intramedullary Lengthening Followed by Osseointegration for Amputees with Short Residual Femurs

Abstract: Context: Some patients seeking transcutaneous osseointegration for amputees (TOFA) have residual bones so short there is concern whether they provide sufficient surface to support full weight. Our strategy was to lengthen these patients' femurs with a motorized intramedullary lengthening nail (MILN) before TOFA. Aims: The aim of this study is to describe 10 transfemoral amputees' experience with MILN before TOFA, focusing on the complications of MILN an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Hip fracture from falls or similar trauma has been reported at 6%; following fracture care, patients regain mobility better than they had in their socket prosthesis [ [29] , [30] , [31] ]. Increasing evidence supports the safety and benefit of osseointegration for an expanding range of patients with lower-extremity issues, notably complex regional pain syndrome [ 32 ], peripheral vascular disease [ 33 ], infection after total knee arthroplasty [ 34 ], burns trauma [ 35 ], very short residual limbs [ 36 , 37 ], irradiated limbs [ 38 ], and patients with hip disarticulation [ 39 ]. Patients with hip arthritis and transfemoral amputation are another important cohort to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Hip fracture from falls or similar trauma has been reported at 6%; following fracture care, patients regain mobility better than they had in their socket prosthesis [ [29] , [30] , [31] ]. Increasing evidence supports the safety and benefit of osseointegration for an expanding range of patients with lower-extremity issues, notably complex regional pain syndrome [ 32 ], peripheral vascular disease [ 33 ], infection after total knee arthroplasty [ 34 ], burns trauma [ 35 ], very short residual limbs [ 36 , 37 ], irradiated limbs [ 38 ], and patients with hip disarticulation [ 39 ]. Patients with hip arthritis and transfemoral amputation are another important cohort to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Expected Outcomes: Review articles describing the clinical outcomes of osseointegration consistently suggest that patients with osseointegrated prostheses have improved prosthesis wear time, mobility, and quality of life compared with patients with socket prostheses. Importantly, studies have shown that osseointegrated prostheses can be utilized in patients with short residual limbs that preclude the use of a socket prosthesis, allowing them to regain or retain function of the joint proximal to the short residuum 5,6 . Osseoperception improves patient confidence during mobility 7 .…”
mentioning
confidence: 99%